A novel experiment-based approach on nonlinear bending analysis of thermoplastic composite laminates. (15th March 2021) - Lu, Taoye; Chen, Xiuhua; Wang, Hai; Zhang, Lei; Zhou, Yinhua
Abstract: A novel experiment-based approach, in which we proposed a new physical model for the carbon fibre reinforced thermoplastic (CFRTP) composite with stress-strain nonlinearity and material bimodularity, is presented for the nonlinear bending analysis of CFRTP composite laminates. The nonlinear stress-strain curves in tension, compression and shear are determined by experiments. The bimodular nonlinear model is validated through comparisons of tensile, compressive and three-point bending experimental data against the finite element analysis results firstly. Numerical investigations are then carried out for the symmetric angle-ply CFRTP composite laminates. The effects of the material nonlinearity, bimodularity, fibre orientation, plate aspect ratio, width-to-thickness ratio, boundary conditions and load distributions on the nonlinear bending load-central deflection and load-bending moment curves of CFRTP laminate plates are discussed in detail.